DIFFERENCES OF STUDENTS’ CHEMISTRY LEARNING OUTCOMES BASED ON THE 5E LEARNING CYCLE MODEL - Defi Elfrida; Rini Selly (JURNAL PENA SAINS, 2023)
The 5E learning cycle model is a learning model that gives opportunities for students to be able to maximize learning by guiding students to be involved in the learning process actively. One of the chemistry concepts that is difficult for students to understand is acid-base topic. This study aims to find out the differences in students' chemistry learning outcomes that apply the 5E learning cycle model by using handouts and PowerPoint-based learning media on acids and bases topic in the eleventh grade of a state senior high school of Medan. This research is included in a quasi-experimental research design with a pretest-posttest control group design. The sample in this study was eleventh grade with experimental class I taught using the 5E learning cycle model assisted by handout media and class experimental II taught using the 5E learning cycle model assisted by PowerPoint-based learning media. Sampling was completed using a random sampling technique. The instrument used in this study was an objective question in the form of multiple choice of 20 questions which had been tested for validity, difficulty level, discriminating, and reliability. The handout media used in this research has been validated by three expert validators and is suitable for use. The result of this research indicates that there are differences between the two classes with the average student learning outcome in experimental class I which was 85,33 compared with the average student learning outcome in experimental class II which is 80,67. Thus, it can be concluded that the 5E learning cycle model using handout media can be applied to the learning process, especially in acid-base topic.